Mycobacterium bovis strain-dependent effects of ESAT-6 and CFP-10 on inflammasome activation in bovine macrophages - Blanco, Federico Carlos (2026)
Mycobacterium bovis, the causative agent of bovine tuberculosis, infects and persists within macrophages, triggering pro-inflammatory responses. While these mechanisms are well characterized for Mycobacterium tuberculosis, less is known about host responses to M. bovis. Inflammasome activation and IL-1β production have been linked to ESAT-6, a substrate of the ESX-1 secretion system present in both species. Here, we examined inflammasome activation in bovine macrophages infected with the virulent M. bovis strain Mb04-303. M. bovis AF2122/97 and NCTC10772 upregulated IL-1β transcription, whereas Mb04-303 and BCG did not. Unexpectedly, deletion of the genes encoding ESAT-6 and CFP-10 from Mb04-303 enhanced inflammasome activation, as evidenced by increased NLRP3 and IL-1β transcription. Complementation with either wild-type ESAT-6/CFP-10 or the T63A ESAT-6 variant restored downregulation of the response, indicating that this substitution does not alter inflammasome modulation. In contrast, deletion of ESAT-6/CFP-10 from an attenuated M. bovis vaccine candidate reduced IL-1β transcription. No differences were observed between M. tuberculosis H37Rv and its ESAT-6-deficient mutant in bovine macrophages. Together, these findings demonstrate that ESAT-6/CFP-10-mediated modulation of inflammasome activation in bovine macrophages is highly dependent on the mycobacterial genetic background.